2011
DOI: 10.1007/s00436-011-2436-y
|View full text |Cite
|
Sign up to set email alerts
|

Do secretions from the uropygial gland of birds attract biting midges and black flies?

Abstract: Bird susceptibility to attacks by blood-sucking flying insects could be influenced by urogypial gland secretions. To determine the effect of these secretions on biting midges and black flies, we set up a series of tests. First, we placed uropygial gland secretions from blue tit Cyanistes caeruleus broods inside empty nest boxes while empty nest boxes without gland secretions were treated as controls. Blue tit broods, from which we had obtained uropygial secretions, were affected by biting midges and black flie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…The function of the uropygial secretions has mainly been framed as preventing feather degradation due not only to microorganisms (see ), but also to environmental conditions and physical abrasion (Moreno‐Rueda, 2011). It has also been suggested that uropygial secretions may attract blood‐suckling insects (Martinez‐de La Puente et al. , 2011) and/or favour symbiotic mites that feed on uropygial secretions smeared on feathers (Galván et al.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the uropygial secretions has mainly been framed as preventing feather degradation due not only to microorganisms (see ), but also to environmental conditions and physical abrasion (Moreno‐Rueda, 2011). It has also been suggested that uropygial secretions may attract blood‐suckling insects (Martinez‐de La Puente et al. , 2011) and/or favour symbiotic mites that feed on uropygial secretions smeared on feathers (Galván et al.…”
Section: Discussionmentioning
confidence: 99%
“…If S. annulus is attracted to uropygial secretions of whooping cranes, we failed to detect it. Similarly, nest boxes baited with uropygial secretions of blue tits ( Cyanistes caeruleus ) and carbon dioxide traps baited with uropygial secretions of feral pigeons ( Columbia livia ) did not increase black fly numbers over controls in Spain (Martinez‐de la Puente et al 2011). However, uropygial secretions of common loons are powerful attractants for S. annulus (Fallis and Smith 1964), although the oils do not evoke a landing response (Smith 3 ).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have found that uropygial secretion attracts mosquitoes (Russell and Hunter, 2005;Garvin et al, 2018b) and blackflies (Fallis and Smith, 1964;Lowther and Wood, 1964;Bennett et al, 1972), either alone or in combination with other stimuli. However, other studies have failed to find any attractant effect (Martínez-de la Puente et al, 2011b;Garvin et al, 2018a;Díez-Fernández et al, 2019 or have found attraction to the secretion only in certain bird or mosquito species, while not in other bird (Garvin et al, 2018b) or mosquito species (Russell and Hunter, 2005). On the other hand, it has even been suggested that uropygial secretion may confer protection against ectoparasites such as lice (Moyer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%